Interplay Between Structural, Electronic, and Magnetic Properties in the d0-d Semi-Heusler Compounds; the Case of the K-Based Compounds - Ozdogan, Kemal; Galanakis, Iosif (MDPI, 2024)
Heusler compounds and alloys represent a rapidly expanding family of materials that exhibit novel properties of significant interest for advanced technological applications. Electronic band structure calculations play a pivotal role in advancing research in this area. In an earlier study, we explored the properties of a new class of Heusler compounds based on Li, referred to as p0-d semi-Heusler Compounds. In this study, we take the research a step further by focusing on d0-d semi-Heusler Compounds, with the chemical formula KZ(Ga, Ge, As, or Se), where Z represents a transition metal. Our investigation centers on the structural, electronic, and magnetic properties of these compounds, particularly in relation to the three possible C1b structures. Most of these compounds are found to be magnetic and, notably, several among them exhibit half-metallicity making them appealing for applications in spintronics. Our findings provide a foundation for future experimental research on these materials.
Keywords: Heusler compounds; ab initio calculations; electronic structure; magnetic materials; Slater-Pauling rule; BAND-STRUCTURE; ALLOYS; COMBINATORIAL; Chemistry; Materials Science